Interval Analysis For Computer Graphics - Snyder, John (ACM SIGGRAPH, 1992)
This paper discusses how interval analysis can be used to solve a wide variety of problems in computer graphics. These problems include ray tracing, interference detection, polygonal decomposition of parametric surfaces, and CSG on solids bounded by parametric surfaces. Only two basic algorithms are required: SOLVE, which computes solutions to a system of constraints, and MINIMIZE, which computes the global minimum of a function, subject to a system of constraints. We present algorithms for SOLVE and MINIMIZE using interval analysis as the conceptual framework. Crucial to the technique is the creation of “inclusion functions” for each constraint and function to be minimized. Inclusion functions compute a bound on the range of a function, given a similar bound on its domain, allowing a branch and bound approach to constraint solution and constrained minimization. Inclusion functions also allow the MINIMIZE algorithm to compute global rather than local minima, unlike many other numerical algorithms. Some very recent theoretical results are presented regarding existence and uniqueness of roots of nonlinear equations, and global parameterizability of implicitly described manifolds. To illustrate the power of the approach, the basic algorithms are further developed into a new algorithm for the approximation of implicit curves.